ECONOMIC GROWTH OF COUNTRIES IN THE REGION SOUTH EAST ASIA IN THE ERA OF THE COVID-19 PANDEMIC - Desi Yuniarti (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
The COVID-19 pandemic has caused a decline in the economy and activity in various sectors and regions in Indonesia. Although the economic shock caused by the COVID-19 pandemic has gradually subsided as the domestic financial market stabilized and several economic sectors expanded. However, given the nature of the blow to both the supply and demand sides of the economy, recovery efforts still need more time. At the same time, the spread of the virus also shows no signs of ending as the trend of confirmed cases and deaths continues to increase. On the one hand, demands for the resumption of various social and economic activities are getting stronger, marked by the loosening of social restrictions in many areas. On the other hand, the existing public health infrastructure is still inadequate. So there is a high risk of re-activating the various wheels of social and economic activities to normal. With these limitations, the new normal is a must. The new normal is also an opportunity to strengthen the economy as long as it is accompanied by transparent priority setting and proper policy coordination and synchronization